Aeronautical Ad Hoc network node failure analysis method - Lixia XIE; Liping YAN; Hongyu YANG (网络与信息安全学报)
To analyze the stability changes of aeronautical ad hoc network (AANET) caused by node failure affecting reaction effectively, an AANET node failure analysis method was proposed.Firstly, the model of business-entity asymmetric dependent network was established based on the characteristics of AANET.Secondly, an improved failure traffic redistribution algorithm was designed to obtain the affected node set.Finally, the AANET affecting impact value was calculated according to the node weight, then the affecting impact degree was determined.The experimental results show that the proposed method has better accuracy in the failure affecting impact analysis of AANET.